Controlling the soundness of Portland cement clinker synthesized with solid wastes based on phase transition of MgNiO2. (July 2022) - Tang, Yanjie; Zhao, Liang; Li, Bo; Chen, Wei
Abstract: A Portland cement clinker containing high content of ferrite phase (>18%) is synthesized with high fractions (60 mass%) of solid wastes, including steel slag, copper tailing, coal gangue and phosphate tailing. Controlling the soundness of clinker caused by the MgO (about 9% in mass) is the key challenge. Adding NiO into the raw meal of clinker controls its soundness via the formation of MgNiO2 with free MgO, showing little effect on the hydration and strength development of cement synthesized with solid wastes. The cement satisfy the 42.5 grade according to the Chinese standard GB 175–2007.